Lipid Profile of Postmenopausal Women with Central Obesity (Journal of Enam Medical College, 2013)
Background: Following menopause there are changes in values of lipid profile parameters. Abdominal obesity has also been linked to significant metabolic abnormalities including changes in lipid parameter values. So, we designed this study to observe the pattern of lipid profile parameters in postmenopausal central obese women.Objective: To assess the lipid profile status of postmenopausal women with central obesity. Materials and Methods: This cross sectional study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during the period of January 2005 to December 2005. Seventy four postmenopausal women with central obesity and age matched 56 nonobese postmenopausal women were included in the study. Central obesity was defined having waist hip ratio more than 0.8. All statistical analyses were done by SPSS 12.0. p values